Fireflies : from pencil to screen. - Tan, Zhong Hong. (2012)
This report outlines the production process of Fireflies, a two-and-a-half minute fully-animated short film marrying 2d and 3d. As this is also meant to be a personal and critical reflection of the project, each section will be accompanied by relevant commentary.